Efektivitas Dan Kontribusi Penerimaan Pajak Hotel Terhadap Pendapatan Asli Daerah Kota Bitung - Raco, Klemens Aldo; Runtu, Treesje; Tangkuman, Steven Josia (Universitas Sam Ratulangi, 2021)
The hotel tax is one part of the local tax which is Bitung City’s Original Local Resource. The purpose of this study is to see how the effectiveness of hotel taxes in Bitung City and how the contribution of hotel tax revenues to Bitung City's Local Revenue. Object for this research is Badan Pendapatan Daerah Kota Bitung. In this research using descriptive qualitative methods, which is collecting, processing and describing data. Research data obtained from literature study and conducted interviews and documentation relevant parties.The results of this research indicate that the effectiveness ofthe hotel tax has reached a very effective level in 2018 and 2019, but is less effective in 2020 and also the hotel taxcontribution is decreasing every year. Bitung Government is expected to socialize about the importance of paying taxes.